A “DECADENT” POET ON THE AESTHETIC “PLANTATIONS” OF THE NEW POETRY - Sorin IVAN (Diversitate si Identitate Culturala in Europa)
The Lost Generation marks a major moment in the development of contemporary Romanian poetry. The process they start and develop in a rebellious manner in the fifth decade is not limited to theoretical o r ideological positions. Advocating the change in poetry, they propose something in return: their own poetry. Another kind of poetry, in the spirit of a new vision and of a new aesthetic, based, paradoxically, on the refusal of aesthetics. The young authors‘ literary offer is remarkable and shows the way to a new kind of poetry, to a new aesthetic canon. Constant Tonegaru is one of the most important poetic voices of this movement, who crystallizes a particular poetic aesthetics. Escapism, fantasy, ir ony and self - irony, bohemian attitudes, intelligence, in an aesthetic context that brings together post - avant - garde, surrealist, neo - modernist and textualist elements, is what defines his aesthetic identity.